HUBUNGAN ASSERTIVENESS TRAINING TERHADAP PERILAKU KEKERASAN DI RUMAH SAKIT JIWA PROF. DR. V. L. RATUMBUYSANG MANADO PROVINSI SULAWESI UTARA - Firmawati Firmawati; Nur Uyuun I. Biahimo (-, 2021)
Violent Behavior is the situation where someone takes an action which can physically harm both him and others. The Objectives of assertiveness training Implementation is to increase the assesment of someone or others, Increase selfesteem and reduce anxiety, Improve ability to make life decisions and express things verbally and nonverbally. The desain of research used descriptive correlation with cross sectional method. The samples are 30 respondents of violent behavior patients using total sampling. Collection tools used questionnaire. This showed that there is a tendency for patients who have less assertiveness training lack severe violent behavior. Result of analysis with chi square test obtained p value = 0,034< a = 0,05 therefore Ho is rejected and Ha is accepted, which showed there is correlation of assertiveness training whit violent behavior. The suggestion to the hospital in order always appilies assertiveness training techniques to reduce violent behavior.